Amelorative effect of olive oil against hepatorenal toxicity of cefotaxime in albino rats - A. A. Elkomy, Ashraf; G. E Elsayed, Mossad; I. El sayed, Faten; A. Abd el atey, Ahmed (International Journal of Pharmacology and Toxicology, 2020)
Due to great hazard effects of antibiotic the following study aimed to investigate the adverse effect of cefotaxime in biochemical, oxidative status and histological examination of Liver and kidney tissue as well as the protective effect of olive oil. Twenty four male Wister albino rats were randomly divided into main four groups including: - G (1): Served as control group and it includes six rats, they were administrated 0.5ml of saline orally for 14 consecutive days. G (2): it includes six rats, they were administered 5ml/kg olive oil orally for 14 consecutive days. G (3): it includes six rats, they were administrated 90mg/kg body weight/twice daily of cefotaxime intramuscular for 14 consecutive days. G (4): it includes six rats, they were administered 5ml/kg olive oil orally concurrently with 90mg/kg body weight/twice daily of cefotaxime. Results revealed that cefotaxime induced significant increases in liver and kidney function parameters including AST, ALT, ALP. creatinine, and urea as well as decrease in albumin and total protein level. Moreover, marked an increase in malondialdehyde (MDA) and decreases in glutathione (GSH) and catalase (CAT) levels. that indicate oxidative stress levels expression in the hepatic and renal tissues following cefotaxime administration. On the beneficial side oral administration of olive oil at the dose 5ml/kg for 14 days significantly mitigate theses toxic effects. So it is concluded that olive oil has great hepatorenal antioxidant effect.Â